PERBEDAAN FONETIK BAHASA MELAYU RIAU DAN BAHASA PELALAWAN - Thiyana Luthfi, Dini; Safitri, Dian; Rahmadika, Della; Mukhlis, Muhammad (UIR Press, 2023)
This article is a study that aims to describe the differences in the Malay language found in the Pelalawan area and the Riau province in the study of phonetics in phonology. This research method uses qualitative research with content approach analysis, such as collecting data and analyzing a data, this research uses interview techniques, note-taking, describes utterances into written language, classifies words into Pelalawan Malay and Riau province Malay which have different pronunciation of phonetic sounds. located at the beginning, middle and end of syllables, classifying the sound or phonetic differences of the Malay pronunciation of the same word based on the area of the speaker, and making conclusions. In this research, residents who live in the area that are the object of research are needed.